The Effect of a Combination of Fly Ash and Manure Pellets on the Amelioration of Latosol Subsoil and Its Impact on the Growth and Yield of Pakcoy (Brassica rapa L.) - Al Hayah, Cauny Nur; Al Haq, Muhammad Izzuddin; Sari, Anis Widia; Agusta, Herdhata (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Fly ash, a solid byproduct of coal combustion, contains both macro- and micronutrients that can function as soil conditioners. This study explores the sustainable use of fly ash in agricultural applications, specifically its role in improving acidic soils. The objective is to evaluate the potential of fly ash based on its chemical properties and agronomic advantages. A quantitative experimental design was applied, incorporating three levels of fly ash and two levels of manure fertilizer combinations, each with four replications plus a control group, resulting in a total of 24 experimental plants. The study assessed various parameters, including pakcoy (Brassica rapa L.) morphological traits (plant height, leaf count, root length, fresh and dry biomass), chemical characteristics of leachates (Ca²⁺, Na⁺, pH, TDS, and EC), photosynthetic performance, and statistical analysis. The results indicated that the treatment (A₂B₂) comprising 35% fly ash, 45% chicken manure, and 20% soil produced the optimal outcomes across all parameters. This treatment led to the best pakcoy growth, characterized by the highest number of leaves, greatest fresh and dry weights, and the longest root development. These findings highlight that fly ash offers a sustainable and effective solution for soil amendment, enhancing agricultural productivity on pakcoy plant by improving soil quality while simultaneously contributing to industrial waste management.